Biodegradable material as well as preparation method and application thereof

By regulating the molecular weight and composition of biodegradable polyester and polylactic acid, combined with the appropriate amount of inorganic filler, the problem of poor edge sealing strength of biodegradable films is solved, and good initial and long-term edge sealing strength is achieved to meet market demand.

CN119823537AActive Publication Date: 2025-04-15KINGFA SCI & TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411980201.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The edge seal strength of biodegradable films, especially the long-term edge seal strength, is poor, which limits its application in logistics express bags, clothing bags, catering bags and food bags.

Method used

By regulating the number average molecular weight of the biodegradable polyester, the number average molecular weight of polylactic acid and the content of D-lactic acid units, and combining with the appropriate amount of inorganic filler, the edge sealing strength and long-term edge sealing strength of the material are improved.

Benefits of technology

It significantly improves the initial edge seal strength and long-term edge seal strength after the biodegradable material is made into a film, meeting the market's demand for good initial edge seal and long-term edge seal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221366140000091
    Figure BDA0005221366140000091
  • Figure BDA0005221366140000101
    Figure BDA0005221366140000101
  • Figure BDA0005221366140000102
    Figure BDA0005221366140000102
Patent Text Reader

Abstract

The invention relates to a biodegradable material as well as a preparation method and application thereof. The biodegradable material comprises the following components in parts by weight: 85-92 parts of biodegradable polyester, 3-8 parts of polylactic acid and 0-8 parts of inorganic filler. Through cooperation of biodegradable polyester with a certain number-average molecular weight and polylactic acid with a certain number-average molecular weight and D-lactic acid unit content, the initial edge sealing strength and long-acting edge sealing strength of a film prepared from the biodegradable material are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material modification, and more specifically, to a biodegradable material and a preparation method and application thereof. Background Art

[0002] Compared with traditional PE, the edge seal strength of biodegradable materials is weaker, especially the long-term edge seal: after the biodegradable film is placed for a week or longer, the edge seal strength drops rapidly, which limits its application in logistics express bags, clothing bags, catering bags and food bags. At present, the market has a strong demand for good initial edge seals and good long-term edge seals: on the one hand, with the development of the industry, lightweight thinning is the general trend of biodegradable film production in the future. Under the trend of thinning, the edge seal strength of biodegradable film has been challenged more; on the other hand, the film products on the market are generally made into films first, and then cut and sealed into products, with a turnover time of 10 days. At the same time, some products are processed into films domestically and then transported to foreign terminals for processing into products, with a turnover time of up to 3 months.

[0003] Currently, there are two main ways to solve the problem of long-term edge sealing in the industry. One is to make the film thicker, which not only affects the use of the product but also increases the cost. The other is to improve the process, such as upgrading the cutter, increasing the temperature, etc. This method has limited effect on improving the edge sealing strength.

[0004] The Chinese patent entitled "A biodegradable material, its preparation method and application" provides a biodegradable material with good edge sealing strength, but does not focus on the long-term edge sealing strength of the material.

[0005] Therefore, it is urgent to develop biodegradable materials with good long-term edge sealing strength to meet market demand. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem of poor edge sealing strength of biodegradable films in the current technology, especially poor long-term edge sealing strength, and to provide a biodegradable material.

[0007] A further object of the present invention is to provide a method for preparing the above biodegradable material.

[0008] A further object of the present invention is to provide use of the above biodegradable material in preparing a film.

[0009] A further object of the present invention is to provide a biodegradable film.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] A biodegradable material comprising the following components in parts by weight:

[0012] 85-92 parts of biodegradable polyester,

[0013] 3-8 parts of polylactic acid,

[0014] Inorganic filler 0-8 parts;

[0015] The biodegradable polyester is a copolymer of a dibasic acid and / or its ester-forming derivative and a diol, and the number average molecular weight of the biodegradable polyester is 50,000 to 100,000;

[0016] The number average molecular weight of the polylactic acid is 60,000 to 160,000, and the content of the D-lactic acid unit in the polylactic acid is 8 to 51 mol%.

[0017] In the present invention, the addition of polylactic acid is to improve the film-forming property of the biodegradable material.

[0018] The inventors of the present invention have found through research that when the number average molecular weight of the biodegradable polyester is regulated within a certain range, the biodegradable polyester molecules can quickly diffuse and entangle under instantaneous high temperature when the film is prepared for edge sealing, thereby improving the edge sealing strength and long-term edge sealing strength. If the number average molecular weight of the biodegradable polyester is too small, although the molecules can still quickly diffuse and entangle during edge sealing, the body strength of the material decreases significantly, resulting in the inability to improve the edge sealing strength; if the number average molecular weight of the biodegradable polyester is too large, it is difficult for the molecules to quickly diffuse and entangle, resulting in difficulty in improving the edge sealing strength.

[0019] In addition, the number average molecular weight of polylactic acid and the content of D-lactic acid units also need to be regulated within a certain range, so as to improve the compatibility of polylactic acid with biodegradable polyester, thereby ensuring the edge sealing strength and long-term edge sealing strength of the biodegradable material.

[0020] In the present invention, inorganic fillers may be added or not. When inorganic fillers are not added, the edge sealing strength and long-term edge sealing strength of the biodegradable material are better. When inorganic fillers are added, the amount added should not be too much to ensure the edge sealing strength and long-term edge sealing strength of the biodegradable material.

[0021] In the present invention, the number average molecular weight and molecular weight distribution coefficient of the biodegradable polyester are tested by GPC using Waters ACQUITY APC TM The equipment was tested at a temperature of 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples, and the results were averaged three times.

[0022] In the present invention, the number average molecular weight and molecular weight distribution coefficient of polylactic acid are tested by GPC using Waters ACQUITY APC TM The equipment was tested at a temperature of 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples, and the results were averaged three times.

[0023] In the present invention, the content of D-lactic acid unit of polylactic acid can be specifically detected according to the following steps: (1) weighing 100±10 mg of ground polylactic acid sample and placing it in a 25 mL pressurized container; (2) adding 10 mL of methanol and 1 drop of dilute sulfuric acid; (3) sealing the pressurized container and placing it in a 150° C. thermostat for 4 hours; (4) taking out the pressurized container and opening the lid after the container cools to room temperature; (5) filtering the sample solution through a membrane filter (pore size 0.22 or 0.45 μm), transferring it to a special injection vial for gas chromatography, and operating according to the instructions of the equipment manufacturer; (6) calculating the content of D-lactic acid unit according to the peak area ratio.

[0024] In the present invention, biodegradable polyester is used as the main resin, and its content accounts for more than 70wt% of the polyester composition.

[0025] In the present invention, the number average molecular weight of the biodegradable polyester may specifically be 50,000, 60,000, 70,000, 80,000, 90,000 or 100,000.

[0026] Biodegradable polyesters copolymerized from commonly used dibasic acids and / or their ester derivatives and commonly used diols in the art can be used in the present invention.

[0027] In the present invention, the biodegradable polyester can be commercially available or homemade.

[0028] Among them, the process of making biodegradable polyester can be as follows:

[0029] The diol, dibasic acid and branching agent are mixed, reacted at 190-220° C. for 2-6 hours, a catalyst is added, and then reacted at 240-260° C. for 4-16 hours to obtain the biodegradable polyester.

[0030] Wherein, the molar ratio of the diol to the dibasic acid is (1.1-2.4):1.

[0031] Preferably, the mass ratio of the dibasic acid to the branching agent is 2.6:(0.001-0.003).

[0032] Preferably, the catalyst includes but is not limited to tetrabutyl titanate.

[0033] Preferably, the branching agent includes but is not limited to glycerol and / or trimethylolpropane.

[0034] Preferably, the dibasic acid is an aliphatic dibasic acid and / or an aromatic dibasic acid.

[0035] More preferably, the aliphatic dibasic acid is at least one of succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid or dodecanedioic acid.

[0036] More preferably, the aromatic dibasic acid is terephthalic acid.

[0037] Preferably, the diol is at least one of butanediol, propylene glycol, ethylene glycol or pentanediol.

[0038] Specifically, the biodegradable polyester can be at least one of polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), polybutylene succinate terephthalate (PBST), polybutylene sebacate adipate terephthalate (PBSeAT), polybutylene sebacate succinate terephthalate (PBSeST), polybutylene succinate adipate terephthalate (PBSAT) or polypropylene adipate terephthalate (PDAT).

[0039] Preferably, in the biodegradable polyester, the repeating units derived from terephthalic acid account for 30 to 55 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0040] Preferably, the molecular weight distribution coefficient of the biodegradable polyester is 1.1 to 3.0.

[0041] More preferably, the molecular weight distribution coefficient of the biodegradable polyester is 2 to 3; more preferably 2.6 to 2.8.

[0042] The molecular weight distribution coefficient is within this range, and the biodegradable polyester contains a certain amount of small molecular weight biodegradable polyester, which can play a wetting role and achieve faster diffusion and entanglement of molecules, thereby making the initial and long-term edge sealing strength of the biodegradable material better.

[0043] In the present invention, the polylactic acid can be obtained commercially or homemade.

[0044] Wherein, the process of making the polylactic acid is as follows:

[0045] Lactide is first reacted in the presence of a catalyst at 130-140° C. and 1000-1400 Pa for 1-6 hours, and then reacted at 160-180° C. and 250-350 Pa for 1-12 hours to obtain the polylactic acid.

[0046] The content of D-lactic acid units in polylactic acid is controlled by controlling the content of D-lactide in the raw material (lactide).

[0047] Wherein, the lactide includes L-lactide and D-lactide, and the mass ratio of L-lactide to D-lactide is 50-80:10-50; the amount of the catalyst used is 0.001% to 1% of the mass of lactide, and the catalyst includes but is not limited to tin-containing compounds (such as stannous octoate).

[0048] Preferably, the molecules of the polylactic acid consist of L-lactic acid units and D-lactic acid units.

[0049] In the present invention, the content of D-lactic acid units in the polylactic acid may specifically be 8, 10, 15, 20, 25, 30, 35, 40, 45 or 50 mol%.

[0050] Preferably, the content of D-lactic acid units in the polylactic acid is 19 to 50 mol%.

[0051] When the content of D-lactic acid units in polylactic acid is controlled within this range, the initial and long-term edge sealing strength of the obtained biodegradable material is better.

[0052] In the present invention, the number average molecular weight of the polylactic acid may specifically be 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000 or 160,000.

[0053] Preferably, the number average molecular weight of the polylactic acid is 60,000-130,000.

[0054] When the number average molecular weight of polylactic acid is controlled within this range, the initial and long-term edge sealing strength of the obtained biodegradable material is better.

[0055] Preferably, the inorganic filler has a D50 particle size of ≤5 μm and a D98 particle size of ≤15 μm.

[0056] More preferably, the inorganic filler has a D50 particle size of 1 to 3 μm and a D98 particle size of 3 to 10 μm.

[0057] When the D50 particle size and D98 particle size of the inorganic filler are regulated within this range, the initial and long-term edge sealing strength of the obtained biodegradable material is better.

[0058] In the present invention, the inorganic filler particle size test method is determined by referring to GB / T 19077.1 "Particle size analysis by laser diffraction method".

[0059] Preferably, the biodegradable material further comprises 0.1 to 2 parts of a compatibilizer. The addition of the compatibilizer can improve the initial and long-term edge sealing strength of the obtained biodegradable material.

[0060] More preferably, the compatibilizer includes but is not limited to styrene-methacrylate copolymers.

[0061] Preferably, the biodegradable material further comprises 0.1 to 3 parts of other auxiliary agents.

[0062] Optionally, the other auxiliary agent is at least one of an antioxidant, a lubricant or a UV stabilizer.

[0063] Usually, the dosage of each other auxiliary agent is: 0.01 to 0.3 parts by weight of antioxidant, 0.1 to 3 parts by weight of UV stabilizer.

[0064] Optionally, the antioxidant is at least one of antioxidant 1010 or antioxidant 168.

[0065] Optionally, the lubricant includes at least one of ethylene bisstearamide, monoglyceride, oleamide or erucamide.

[0066] Optionally, the UV stabilizer is at least one of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate or 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-(2,4-dimethylphenyl)-2H-benzotriazol-4-one.

[0067] The method for preparing the above-mentioned biodegradable material comprises the following steps:

[0068] The components are mixed and melt-extruded to obtain the biodegradable material.

[0069] Preferably, the temperature of the melt extrusion is 150-170° C.; the screw length-to-diameter ratio of the melt extruder is 35-45:1, and the screw speed is 300-400 rpm.

[0070] Application of the above biodegradable material in the preparation of biodegradable films or bags.

[0071] A biodegradable film or bag is made from the above biodegradable film.

[0072] Compared with the prior art, the present invention has the following beneficial effects:

[0073] The invention significantly improves the initial edge sealing strength and long-term edge sealing strength of the film made of the biodegradable material by combining a biodegradable polyester with a certain number average molecular weight and a polylactic acid with a certain number average molecular weight and D-lactic acid unit content. DETAILED DESCRIPTION

[0074] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0075] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0076] Biodegradable polyester 1#: Homemade, polybutylene adipate terephthalate, the preparation method is as follows:

[0077] 1.8 kg of terephthalic acid, 2.0 kg of adipic acid, 2.6 kg of 1,4-butanediol (excess), and 2.0 g of glycerol were added to a 20 L reactor, stirred at 190°C (temperature T1) for 3 hours (time t1), and then 0.01% of tetrabutyl titanate in total molar ratio of acid to alcohol was added as a catalyst, the temperature was raised to 240°C (temperature T2), vacuum was opened, and the reaction was carried out for 8 hours (time t2), thereby obtaining biodegradable polyester 1#. The number average molecular weight (M) of biodegradable polyester 1# n ) is 70028, and the molecular weight distribution coefficient (M W / M n ) is 2.0, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0078] Biodegradable polyester 2#: homemade, polybutylene adipate terephthalate, the preparation method thereof is different from that of biodegradable polyester 1# in that the time t1 is 2 hours and the time t2 is 4 hours. The number average molecular weight (M n ) is 55872, and the molecular weight distribution coefficient (M W / M n ) is 2.2, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0079] Biodegradable polyester 3#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 6 hours and the time t2 is 16 hours. The number average molecular weight (M n ) is 97520, and the molecular weight distribution coefficient (M W / M n ) is 1.9, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0080] Biodegradable polyester 4#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that: 3.0g of glycerol. The number average molecular weight (M n ) is 70338, and the molecular weight distribution coefficient (M W / M n ) is 2.8, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0081] Biodegradable polyester 5#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that: 1.5g of glycerol. The number average molecular weight (M n ) is 70580, and the molecular weight distribution coefficient (M W / M n ) is 1.6, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0082] Biodegradable polyester 6#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that: 2.4 kg of terephthalic acid. The number average molecular weight (M n ) is 70610, and the molecular weight distribution coefficient (M W / M n ) is 2.1, and the repeating units derived from terephthalic acid account for 54 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0083] Biodegradable polyester 7#: homemade, polybutylene sebacic acid terephthalate, the preparation method is different from that of biodegradable polyester 1# in that adipic acid is replaced by sebacic acid (2.0 kg). The number average molecular weight (M n ) is 70090, and the molecular weight distribution coefficient (M W / M n ) is 2.0, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0084] Biodegradable polyester 8#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that: 1.0 g of glycerol. The number average molecular weight (M n ) is 70921, and the molecular weight distribution coefficient (M W / M n) is 1.1, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0085] Biodegradable polyester 9#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 1 hour and the time t2 is 3 hours. The number average molecular weight (M n ) is 41072, and the molecular weight distribution coefficient (M W / M n ) is 2.1, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0086] Biodegradable polyester 10#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 8 hours and the time t2 is 20 hours. The number average molecular weight (M n ) is 125730, and the molecular weight distribution coefficient (M W / M n ) is 2.0, and the repeating units derived from terephthalic acid account for 45 mol% of the sum of the repeating units derived from terephthalic acid and the repeating units derived from the dibasic acid.

[0087] Polylactic acid 1#: homemade, its preparation method is as follows: PLLA / PDLA copolymer, homemade, 80 parts by weight of pure L-lactide (L content ≥ 99.5%, the same below) and 20 parts by weight of pure D-lactide (D content is about 50%, the same below) are mixed, stannous octoate (0.1wt% relative to the total amount of lactide) is added, and ring-opening polymerization is carried out, first at a reaction temperature of 135°C and a reaction pressure of 1200Pa for 4 hours (time t3), and then at a reaction temperature of 170°C and a reaction pressure of 300Pa for 6 hours (time t4). Underwater pelletizing, crystallization, and drying give polylactic acid 1#. The number average molecular weight of polylactic acid 1# is 125830, and the content of D-lactic acid unit is 19.8%.

[0088] Polylactic acid 2#: Homemade. The difference between its preparation method and that of polylactic acid 1# is that the amount of pure L-lactide is 90 parts by weight and the amount of pure D-lactide is 10 parts by weight. The number average molecular weight (M n ) is 129987, and the D content is 9.7%.

[0089] Polylactic acid 3#: Homemade. The difference between its preparation method and that of polylactic acid 1# is that the amount of pure L-lactide is 50 parts by weight and the amount of pure D-lactide is 50 parts by weight. The number average molecular weight (Mn ) is 124926, and the content of D-lactic acid units is 49.7%.

[0090] Polylactic acid 4#: homemade. The difference between its preparation method and that of polylactic acid 1# is that the time t3 is 2 hours and the time t4 is 3 hours. The number average molecular weight (M n ) is 64332, and the content of D-lactic acid units is 19.8%.

[0091] Polylactic acid 5#: homemade. The difference between its preparation method and that of polylactic acid 1# is that the time t3 is 6 hours and the time t4 is 12 hours. The number average molecular weight (M n ) is 159976, and the content of D-lactic acid units is 19.8%.

[0092] Polylactic acid 6#: homemade, its preparation method is different from that of polylactic acid 1# in that time t3 is 8 hours and time t4 is 15 hours. The number average molecular weight (M n ) is 193970, and the content of D-lactic acid units is 19.9%.

[0093] Polylactic acid 7#: Homemade. Its preparation method is different from that of polylactic acid 1# in that it is synthesized using 98 parts by weight of pure L-lactide and 2 parts by weight of pure D-lactide. The number average molecular weight (M n ) is 126985, and the content of D-lactic acid unit is 1.9%.

[0094] The content of D-lactic acid units in polylactic acid can be specifically detected according to the following steps: (1) Weigh 100±10 mg of ground polylactic acid sample and place it in a 25 mL pressurized container; (2) Add 10 mL of methanol and 1 drop of dilute sulfuric acid; (3) Seal the pressurized container and place it in a 150°C thermostat for 4 hours; (4) Take out the pressurized container and open the lid after the container cools to room temperature; (5) After filtering the sample solution through a membrane filter (pore size 0.22 or 0.45 μm), transfer it to a special injection vial for gas chromatography and operate according to the equipment manufacturer's instructions; (6) Calculate the content of D-lactic acid units based on the peak area ratio.

[0095] The inorganic filler is obtained from the following raw materials with or without grinding and / or sieving.

[0096] Inorganic filler 1#: calcium carbonate, Xinrong, ACC-815, D50 is 1.6μm, D98≤8.4μm;

[0097] Inorganic filler 2#: talcum powder, Guangxi Longsheng Huamei Talc Development Co., Ltd., D50 is 2.5μm, D98≤4μm;

[0098] Inorganic filler 3#: calcium carbonate, TECO, DY-66N36, D50 is 4.1μm, D98≤14.1μm;

[0099] The particle size of inorganic fillers can be determined by referring to GB / T 19077.1 "Particle size analysis by laser diffraction method".

[0100] Compatibilizer: styrene-methacrylate copolymer, Jiayirong, HPC-3510P;

[0101] Other additives 1#: ethylene bis stearamide, commercially available;

[0102] Unless otherwise specified, the components (such as other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.

[0103] The biodegradable materials provided in the embodiments and comparative examples of the present invention are firstly respectively passed through a film blowing machine, and the pulling speed is adjusted to form a film with a thickness of 40 μm. The film is edge-sealed at 350° C. and the speed is set to 80 pieces / min. The performance of the edge-sealed film is measured according to the following test method:

[0104] 1) Grade of initial edge seal strength: The edge seal strength is tested by tensile strength. The tensile fracture position is prone to occur at the non-sealed position, so the hand-tear edge seal grade is used for evaluation. The evaluation criteria are shown in Table 1: The higher the grade, the better the edge seal strength. Each film of the embodiment and the comparative example is tested 20 times on average, and the average value is calculated.

[0105] Table 1

[0106]

[0107] 2) Grade of long-term edge seal strength: The biodegradable materials of each embodiment and comparative example were made into a film with a thickness of 40 μm, and edge-sealed at 350° C. and 80 pcs / min. After edge-sealing, the film was placed in an environment of 25° C. and 55% RH for 3 months, and then the grade of long-term edge seal strength was evaluated according to the evaluation method of the grade of initial edge seal strength.

[0108] The biodegradable materials of the embodiments and comparative examples of the present invention are prepared by the following preparation method:

[0109] Weigh each component according to the formula, mix the components evenly, and then put them into a twin-screw extruder for melt extrusion and granulation to obtain a biodegradable material. The temperatures of zones 1 to 10 of the twin-screw extruder are 150°C, 155°C, 160°C, 165°C, 165°C, 165°C, 165°C, 165°C, 170°C and 170°C, respectively; the screw aspect ratio is 40:1, and the screw speed is 300rpm.

[0110] Examples 1 to 16

[0111] Examples 1 to 16 provide a series of biodegradable materials, the formulations of which are shown in Tables 2 and 3.

[0112] Table 2 Formulations of Examples 1 to 10 (parts by weight)

[0113]

[0114] Table 3 Formulas of Examples 11 to 16 (parts by weight)

[0115]

[0116]

[0117] Comparative Examples 1 to 4

[0118] Comparative Examples 1 to 4 provide a series of biodegradable materials, and their formulations are shown in Table 4.

[0119] Table 4 Formulas of Comparative Examples 1 to 4 (parts by weight)

[0120]

[0121] The properties of the biodegradable materials of the embodiments and comparative examples were tested according to the above-mentioned test methods. The test results are shown in Table 5.

[0122] Table 5 Performance test results of biodegradable materials of various embodiments and comparative examples

[0123]

[0124]

[0125] From Table 5, we can see that:

[0126] The initial edge sealing strength of the biodegradable materials of Examples 1 to 16 was above 4.3, and the long-term edge sealing strength was above 3.0, indicating that the biodegradable materials of the present invention not only have good initial edge sealing strength, but also have good long-term edge sealing strength.

[0127] The number average molecular weight of the biodegradable polyester added in Comparative Examples 1 and 2 is too small or too large, and the initial edge sealing strength of the biodegradable materials is poor. The long-term edge sealing strength of the biodegradable material in Comparative Example 1 is not good, and the long-term edge sealing strength of the biodegradable material in Comparative Example 2 is poor. The number average molecular weight of the polylactic acid added in Comparative Example 3 is too large, and the D content of the polylactic acid added in Comparative Example 4 is too low. The biodegradable materials obtained by the two methods have poor initial edge sealing strength and poor long-term edge sealing strength.

[0128] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A biodegradable material, characterized in that: The composition comprises the following components in parts by weight: 85-92 parts of biodegradable polyester, 3-8 parts of polylactic acid, Inorganic filler 0-8 parts; The biodegradable polyester is a copolymer of a dibasic acid and / or its ester-forming derivative and a diol, and the number average molecular weight of the biodegradable polyester is 50,000 to 100,000; The number average molecular weight of the polylactic acid is 60,000 to 160,000, and the content of the D-lactic acid unit in the polylactic acid is 8 to 51 mol%.

2. The biodegradable material according to claim 1, characterized in that: The dibasic acid is an aliphatic dibasic acid and / or an aromatic dibasic acid.

3. The biodegradable material according to claim 1, characterized in that: The diol is at least one of butanediol, propylene glycol, ethylene glycol or pentanediol.

4. The biodegradable material according to claim 1, characterized in that: The molecular weight distribution coefficient of the biodegradable polyester is 1.1-3.

0.

5. The biodegradable material according to claim 1, characterized in that: The inorganic filler has a D50 particle size of ≤5 μm and a D98 particle size of ≤15 μm.

6. The biodegradable material according to claim 1, characterized in that: The biodegradable material also includes 0.1 to 1 part of a compatibilizer.

7. The biodegradable material according to claim 1, characterized in that: The biodegradable material also includes 0.1 to 2 parts of lubricant.

8. The method for preparing the biodegradable material according to any one of claims 1 to 7, characterized in that: The steps include: The components are mixed and melt-extruded to obtain the biodegradable material.

9. Use of the biodegradable material according to any one of claims 1 to 7 in the preparation of biodegradable films or bags.

10. A biodegradable film or bag, characterized in that: Made from the biodegradable material described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Biodegradable material and preparation method thereof

    CN115403902A

  • Biodegradable material as well as preparation method and application thereof

    CN117343505A

  • Biodegradable card

    JP1996290693A

  • Aliphatic polyester composition

    JP1997272789A

  • Biodegradable polyester film and method for producing the same

    JP2004315659A